THE IDEATIONAL MEANING REALISED IN THE WRITTEN DISCOURSE IN ONLINE NEWSPAPER ON ABDUL QODIR JAELANI (AQJ) (English Education Journal, 2014)
This thesis is aimed at reporting the analysis on the ideational meaning realised in the written discourse in online newspaper on Abdul Qodir Jaelani (AQJ). Under a discourse analysis method, the data were collected through retrieving twenty texts on the discourse of AQJ from some online newspapers. The texts on the discourse of AQJ are analysed using the framework of systemic functional linguistics which is realised based on the ideational meaning as suggested by Halliday & Matthiessen (2004). The findings reveal that there are 1043 participant types (2%) involve throughout the texts. Meanwhile, there are 712 process types (3%) involve, and there are 274 circumstance types (7%) involve throughout the texts. Hence, the existence of participants is more dominant than processes and circumstances available throughout twenty texts. Based on the findings, it is recommended that the English teacher can apply discourse analysis as the approach to analyse the texts in teaching the English learners about how to analyse the clauses of the texts to enhance their ability in analysing the text both journalistic texts (hard and soft news) and classroom texts (text types).